2016
DOI: 10.1159/000444933
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid A Type 1 Gene Polymorphism in Egyptian Children with Familial Mediterranean Fever

Abstract: Background: Since spontaneous inflammation is an important contributor to familial Mediterranean fever (FMF), genetic variants mediating inflammation are of interest. We investigated gene variants in the acute-phase serum amyloid A type 1 (SAA1), a sensitive marker of inflammatory activity, and their association with susceptibility and severity of FMF. Methods: The genotypes of 2 single-nucleotide polymorphisms within exon 3 of SAA1 (2995C/T and 3010C/T) were determined in 105 Egyptian children with FMF and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
3
0
5
Order By: Relevance
“…M694I mutation has been associated with severe and uncommon clinical picture, including renal involvment and erysipelas‐like erythema, respectively . Particularly, the M694I/M694I genotype, identified in 52% patients, was significantly associated with the development of amyloidosis in Algerians and Arabs .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…M694I mutation has been associated with severe and uncommon clinical picture, including renal involvment and erysipelas‐like erythema, respectively . Particularly, the M694I/M694I genotype, identified in 52% patients, was significantly associated with the development of amyloidosis in Algerians and Arabs .…”
Section: Resultsmentioning
confidence: 99%
“…[71][72][73][74] M694I mutation has been associated with severe and uncommon clinical picture, including renal involvment and erysipelas-like erythema, respectively. 75 Particularly, the M694I/M694I genotype, identified in 52% patients, was significantly associated with the development of amyloidosis in Algerians and Arabs. 68 Authors also described a relationship between the M694I mutation and a higher prevalence of serositis and familial aggregation in Japanese patients with FMF.…”
Section: Clinical Phenotype and Gene Variants In Exon 10mentioning
confidence: 92%
“…Disease severity scores are now used in many diseases to evaluate disease severity more objectively. In previous studies, it was found that the disease severity scores showed more severe disease in the group carrying the homozygous M694V mutation (13)(14)(15). However, in a study from Turkey, it was observed that carrying the M694V mutation in one allele or two alleles did not change the severity of the disease (16).…”
Section: Discussionmentioning
confidence: 92%
“…Birçok araştırmada homozigot M694V mutasyonunun hastalığın daha erken başlamasına ve ciddi tablolar ile sonuçlanmasına neden olacağı öne sürülmüş olup bu mutasyonu taşıyan hasta grubunda diğer gruplardan daha yüksek hastalık ağırlık skoru gösterilmiştir (2,13,21,22). Çalışmamızda da benzer olarak en yüksek hastalık ağırlık skorları M694V mutasyonunu homozigot taşıyan grupta bulundu.…”
Section: Discussionunclassified